Gallium oxide-based solar-blind ultraviolet photodetectors. (17th January 2020) - Chen, Xuanhu; Ren, Fang-Fang; Ye, Jiandong; Gu, Shulin
Abstract: Gallium oxide (Ga2 O3 ) is an emerging ultrawide bandgap (UWBG) semiconducting material as a key building block for the applications of power electronics, solar blind photodetectors and deep ultraviolet optoelectronics beyond existing technologies. To date, solar-blind photodetectors based on Ga2 O3 in the various forms of bulk crystals, epitaxial thin films, nanostructures, and heterostructures have been demonstrated with either high performance or multiple functionalities, however, several remaining challenges require proper solutions for practical applications. In this topic review, we summarized recent advances in processing and device performance of solar photodetectors based on Ga2 O3 and the associated physical mechanisms behind according to the architecture of photodetectors. The feasibility of p -type doping, the defect behavior, and radiation effects on the device performance have been discussed. The demonstration of novel and advanced architectures such as phototransistors, highly narrow-band photodetectors, photodetector arrays, and integrated NEMS resonance oscillators for real-time ultraviolet light detection are included. This review may provide better understanding on the optoelectronics properties of the Ga2 O3 emerging material to fully exploit its promising optoelectronic applications in deep ultraviolet spectral region.